Interest, design and assessment of eco-industrial parks in China within a circular economy paradigm - Xing, J.; Vilas-Boas da Silva, J. M.; Duarte de Almeida, I (Proceedings of the 21st Cambridge International Manufacturing Symposium, 2017)
This descriptive research addresses sustainability developments within circular economy (CE). Firstly, a 7R framework that provides an updated base to assess, develop and compare Eco-Industrial Parks (EIPs) was developed and preliminarily checked with secondary data from the Suzhou Industrial Park, which enables relevant benchmarking among EIPs all over the world. Secondly, different typologies of industrial parks in China provinces were analysed and related role changes were described. The 13th Five-Year Plan on National Economic and Social Development, called for the third generation of EIPs, as enablers of sustainability and balanced development of urbanization in an eco-city that combines industrial growth with city development. Therefore, Corporate, Consumer and Citizen Social Responsibility (coined as 3CSR) are attached to pursuing economic growth, social progress, and environmental sustainability. This research sets the scene for significant CE future developments, by leveraging the role of modern eco-cities through EIPs guided by a new conceptual model (7R).